Improving EFL Students’ Higher Order Thinking Skills Through Collaborative Strategic Reading in Indonesia - Arik Susanti; Pratiwi Retnaningdyah; Ade Nila Puspita Ayu; Anis Trisusana (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
The study aims to investigate whether collaborative strategic reading (CSR) strategies can improve higher-order thinking skills (HOTS) of students. It is an experimental design using pre-test and post-test as an instrument. Research data was obtained by giving a reading test in one of the public vocational high schools in Surabaya, Indonesia. These test data were analyzed using independent sample T-test and paired sample T-test in SPSS. Results showed that Collaborative Strategic Reading (CSR) could improve higher-order thinking skills for students. Based on data analysis results, t count was found to be larger than t table. Moreover, the result of the paired-sample t-test also indicated a significant difference between pre-test and post-test scores of experimental students. Sig. Sig. (2-tailed) equals.000. To sum up, the strategy benefits students in enhancing higher-order thinking skills for students.